Kuwait: Islamic banking for a consumer society - Wilson, Rodney (Islamic financial markets, 1990)
The Kuwait Finance House was established in 1977. It was set up as an Islamic investment bank, operating under a special government decree which recognized the Islamic nature of the institution. The article reviews its experience, examining its activities, performance, profitability, liquidity positions, and returns to depositors and investors. (DÜI-Ott)